A novel function for the Mre11-Rad50-Xrs2 complex in base excision repair - Steininger, Sylvia (Oxford University Press, 2010)
The Mre11/Rad50/Xrs2 (MRX) complex in Saccharomyces cerevisiae has well-characterized functions in DNA double-strand break processing, checkpoint activation, telomere length maintenance and meiosis. In this study, we demonstrate an involvement of the complex in the base excision repair (BER) pathway. We studied the repair of methyl-methanesulfonate-induced heat-labile sites in chromosomal DNA in vivo and the in vitro BER capacity for the repair of uracil- and 8-oxoG-containing oligonucleotides in MRX-deficient cells. Both approaches show a clear BER deficiency for the xrs2 mutant as compared to wildtype cells. The in vitro analyses revealed that both subpathways, long-patch and short-patch BER, are affected and that all components of the MRX complex are similarly important for the new function in BER. The investigation of the epistatic relationship of XRS2 to other BER genes suggests a role of the MRX complex downstream of the AP-lyases Ntg1 and Ntg2. Analysis of individual steps in BER showed that base recognition and strand incision are not affected by the MRX complex. Reduced gap-filling activity and the missing effect of aphidicoline treatment, an inhibitor for polymerases, on the BER efficiency indicate an involvement of the MRX complex in providing efficient polymerase activity.